Development of long term use of psychotropic drugs by general practice patients. Issue 6617 (23rd January 1988) - Mant, Andrea; Duncan-Jones, Paul; Saltman, Deborah; Bridges-Webb, Charles; Kehoe, Linda; Lansbury, Gwenda; Chancellor, Alan H B
Abstract : From 1984 to 1986 a prospective study was conducted of 104 general practice patients who started treatment with a benzodiazepine or an antidepressant drug. The duration of reported use of the drugs was two months for 45% of patients, four months for 17% of patients, and six months for 15%. Type of drug, age, and level of education were found to be predictive of continuing use. General practitioners have a significant effect on their patients' use of drugs and, with careful selection and review when prescribing, may help to prevent dependence on psychotropic drugs.